Australia's Pharmacology Research: A Scientometric Assessment of High-Cited Papers During 2002–2021. Issue 4 (December 2022) - Ahmed, K.K. Mueen; Gupta, B.M.; Mamdapur, Ghouse Modin
Objectives: To analyze Australia's high-cited papers (HCPs) receiving ≥100 citations in pharmacology during 2002–2021 and examine the research characteristics, study performance of the top 30 leading participating organizations and authors, and identification of top 30 journals publishing in this area and sub-fields of their research. Materials and Methods: Australia's HCPs on pharmacology research from the top 30 most productive organizations were identified and extracted from the Scopus database from 2002 to 2021 on 21 September 2022 using a search strategy. Select bibliometric measures were utilized to evaluate the publication productivity of important players in this area. The network analysis was performed to evaluate the collaborative interactions amongst the countries, organizations, authors, and keywords. Results: Of the 19, 418 Australia's publications (articles) in pharmacology from the top 30 most productive organizations during 2002–2022, only 685 (3.53%) were HCPs, which together received 1, 14, 623 citations, averaging 164.4 citations per paper (CPP) and the citations ranged from 100 to 1, 230. Two papers had more than 1, 000 citations and 16 papers had 500 citations. Of the 685 HCPs, 40.58% (278) and 11.39% (78) received external funding support and were international collaboratives. The most productive organizations were Monash University (n = 155), the University of Queensland (n = 111) and the University of Melbourne (n = 97). The most impactful organizations in terms of CPP and relative citation index (RCI) were James Cook University (203.22 and 1.21), Australian National University (196.67 and 1.18) and Queensland University of Technology (193.45 and 1.16). The most productive authors were J. Li (n = 24), C. J. H. Porter (n = 24) and R. L. Nation (n = 23) (Monash University, Melbourne); and the most impactful authors in terms of CPP were A. Christopoulos (Monash Institute of Pharmaceutical Sciences, Melbourne) (288.21), C.W. Pouton (Monash University, Melbourne) (241.50), and D.L. Peterson (University of Queensland, Brisbane) (225.58). The most productive journals were Antimicrobial Agents and Chemotherapy (n = 59), Environmental Pollution (n = 43) and Journal of Medicinal Chemistry (n = 42). The most impactful journals in terms of CPP were Nature Reviews Drug Discovery (371.8), Antiviral Research (286.86) and European Journal of Pharmaceutical Sciences (253.0). The most important keywords with their frequency of appearances were Animal Experiments (108), Metabolism (76), Drug Effects (67), Animal Models (65), Protein Expression (64), Anti-Bacterial Agents (62), Drug Delivery Systems (54), Drug Formulation (44), Signal Transduction (42), and so on. Conclusion: There is an urgent need to increase national funding and expand international collaboration in priority areas, which will help to increase and diversify research output and improve research impact.